PERENCANAAN PEMBANGKIT LISTRIK HYBRID VAWT DAN SOLAR CELL SECARA OTOMATIS UNTUK PENERANGAN LAMPU JALAN - Herri Darsan; Dwi Prabowo; Maidi Saputra; Murhaban Murhaban (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2020)
Road lighting is important for transportation activities, especially at night. The design of this Hybrid plant has a working principle that is utilizing wind gusts from a passing vehicle to turn the turbine blade and the heat of solar radiation that is absorbed through the solar panel with the sun tracking system. Parameter data that influence in the design of Hybrid Generations are variations in the number of turbine blades, turbine angle, wind speed, turbine drive rotor height, density of air and heat of solar radiation. The purpose of the problem in Designing Hybrid VAWT generating systems with the optimal angle of the turbine and Solar Cell automatically to be able to meet the electrical energy requirements for street lighting. The research method used in design through three stages, namely literature review, Technical Design and preparation of work tools and materials. The design results show that the optimal type u vertical wind turbine for toll road lighting with 3 blades and an optimal angle size of 90 0C, rotor diameter of 400 mm, rotor height of 1000 mm for average wind speed of 13.9 m / s. and Average solar heat of 28 0C with an average panel temperature of 55.3 0C using the Timer switch as a solar tracking system. The design of the plant, produces turbine power of 0.93 V to 1.17 V at 122 rpm to 214 rpm. And the solar panel produces a panel voltage of 19.59 V and an average voltage on the battery of 14 V. The stored electrical energy is able to light two LED lights with a power of 15 Watt and last for 12 hours / dayKeywords— Hybrid Power Generation, Optimal Angle, Timer Switch